PENGARUH KUALITAS PRODUK PERSEPSI HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA BENGKEL PLANET BAN RAYA DALUNG - Maharani, Anak Agung Istri Eva (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2024)
Optimizing customer satisfaction is still one of the efforts in retaining Planet Tire Raya Dalung Workshop customers. Customer satisfaction is influenced by many factors. Some of these factors include product quality, price perception, and service quality. The formulation of the problem in this study is whether product quality, price perception and service quality partially and simultaneously affect customer satisfaction at Planet Ban Raya Dalung Workshop. The purpose of this study was to determine the effect of product quality, price perception, and service quality partially and simultaneously on customer satisfaction at the Planet Ban Raya Dalung workshop. The number of samples was determined by purposive random sampling technique with a sample of 85 respondents. Data analysis technique using validity and reliability test, classic assumption test, multiple linear regression analysis, determination analysis, partial significant test (T-test) and simultaneous significant test (F-test). The results showed that there was a positive and significant effect partially or simultaneously between product quality, perceived price and service quality on customer satisfaction of Planet Ban Raya Dalung.